Woman As Prophet in the Home and the World : Interdisciplinary Investigations. - Lemmons, R. Mary Hayden; Andrews, Peggy; Dalessio, Christine Falk.; Eberstadt, Mary.; Flood, Anthony T.; Giebel, Heidi; Karraker, Meg Wilkes; King, Anne.; Kucharski, Paul.; Savage, Deborah (Lanham : Lexington Books/Fortress Academic, 2016)
This first-ever interdisciplinary study of the woman as prophet shows that, in these troubling times, ordinary women--especially Christian women--need to function as prophets by proclaiming, in word and deed, the indispensability of lovingly seeking the welfare of others.
Intro -- Contents -- Acknowledgments -- Latin Titles, Abbreviations, and Translations -- Introduction -- Part I: The Prophetic Feminine Genius: Cognitive and Ontological Dimensions -- 1 St. John Paul II on the Genius of Woman -- 2 On Women and the "Seeing" of Others -- Part II: Recasting Feminism and Femininity as Prophecy -- 3 The Feminine Genius, Personalist Feminism, and the Call for Women to Prophesy according to John Paul II -- 4 Woman as Prophet -- 5 The New Feminism, Prophetic Bodies, and Freedom -- 6 Prophetic Femininity in the Bible, the Church, and Nature -- Part III: The Spirituality of Women Prophets -- 7 Worthy of Belief -- 8 St. Hildegard -- 9 Women Mystics of the Catholic Church -- Part VI: Meeting Key Personal, Professional, and Cultural Challenges -- 10 Women and the Crises of Polarization and Secularization -- 11 The Destructiveness of Lust and Its Cure -- 12 The Logic of the Gift -- 13 How Mothers with Professional Careers Experience the State of Flourishing, and Why It Matters for Faith Communities -- 14 Spirit in the Heartland -- Afterword -- Index -- About the Contributors.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Women prophets; Electronic books